Design and evaluation of a touchscreen apparatus for operant research with pigeons. Issue 2 (8th July 2021) - Toegel, Forrest; Toegel, Cory; Perone, Michael
Abstract : We developed a touchscreen apparatus for pigeons and conducted a series of experiments that assessed its utility for free‐operant procedures. The apparatus incorporated an on‐board Windows computer, an electromechanical interface, an amplified speaker, and the touchscreen. We found that merely projecting a virtual key on the screen was insufficient; too many pecks missed the key. Adding a visual target in the center of the key and providing visual feedback for on‐key pecks both failed to improve response accuracy. Accuracy was improved by imposing a timeout after off‐key pecks or providing a physical boundary around the key. With the physical boundary, response accuracy was comparable to that obtained with conventional plastic keys, and response acquisition via autoshaping also was comparable. Mixing the color elements of the screen's pixels produced color stimuli, but the colors did not function as pure wavelengths of light in tests of stimulus generalization. Both colors and geometric shapes functioned as discriminative stimuli in multiple schedules with variable‐interval and extinction components or rich and lean fixed‐ratio components. In general, our touchscreen apparatus is a viable alternative to conventional pigeon chambers and increases the experimenter's options for visual stimuli, auditory stimuli, and the number and location of response keys.